Medicinal plants and natural products in amelioration of arsenic toxicity: a short review - Sanjib Bhattacharya (Taylor & Francis Group, 2017)
Context: Chronic arsenic toxicity (arsenicosis) is considered a serious public health menace worldwide, as there is no specific, safe, and efficacious therapeutic management of arsenicosis. Objectives: To collate the studies on medicinal plants and natural products with arsenic toxicity ameliorative effect, active pre-clinically and/or clinically. Methods: Literature survey was carried out by using Google, Scholar Google and Pub-Med. Only the scientific journal articles found on the internet for last two decades were considered. Minerals and semi-synthetic or synthetic analogs of natural products were excluded. Results: Literature study revealed that 34 medicinal plants and 14 natural products exhibited significant protection from arsenic toxicity, mostly in preclinical trials and a few in clinical studies. Conclusion: This research could lead to development of a potentially useful agent in clinical management of arsenicosis in humans.